Pengawasan Klien Di Balai Pemasyarakatan Kelas I Surabaya Di Masa Pandemi COVID-19 - Soemanto, Rizki Anggerda Lopez; Astuti, Pudji (NOVUM : JURNAL HUKUM, 2021)
Abstract The emergence of the coronavirus disease (COVID-19) outbreak has shocked the world. The government is also trying to prevent and control the spread of the virus by imposing Large-Scale Social Restrictions. Another effort made by the government is to provide assimilation and integration of prisoners / children on the grounds that prisons / LPKA / detention centers are over-capacity. The purpose of this research is 1) to find out the implementation of supervision carried out by the Community Guidance of Clients at the Class I Correctional Center Surabaya during the COVID-19 pandemic based on the Circular of the Directorate General of Corrections Number: PAS-20.PR.01.01 Year 2020, 2) to know and explained the obstacles experienced by Community Advisors in implementing Client supervision at the Class I Correctional Center in Surabaya during the COVID-19 pandemic. This research uses sociological juridical research methods. . Therefore, the Ministry of Law and Human Rights of the Republic of Indonesia, the Directorate General of Corrections issued a Circular, with Circular Number: PAS-20.PR.01.01 Year 2020 concerning Progressive Steps in Combating the Spread of the Corona Disease Virus (COVID-19) in the Implementing Unit Correctional Technical. Keywords: Client Supervision, Correctional Facilities, COVID-19 Pandemic